VARIASI SUARA PANGGILAN KODOK HYLARANA NICOBARIENSIS (STOLICZKA, 1870) DARI LIMA POPULASI BERBEDA DI INDONESIA (ANURA: RANIDAE) - Kurniati, Hellen; Hamidy, Amir (Perhimpunan Biologi Indonesia, 2016)
Hylarana nicobariensis (Stoliczka, 1870) is a very common frog, which has a wide distribution, covering the southern part of Thailand, Peninsular Malaysia, Sumatra, Borneo, Java, Bali and Palawan in the Philippines. The presence of this frog is very easy to be recognized by listening its shrill call that is sounded loudly all day. Detailed descriptions of H. nicobariensis?s calls from Ulu Gombak in Peninsular Malaysia and Danum Valley in Sarawak have been published by Jehle and Arak (1998), which are some call characters of the frog from the two locations are significantly different. To determine the call characters that can distinguish among populations of this frog, advertisement calls of five different populations (Batukaru, Curup, Limau Manis, Curug Nangka and Lake Ecology Park) were analyzed. The characters of the call waves on the five populations are different in the structure of sub-pulses, dominant frequency and lower frequency. Among the five populations, the population from Lake Ecology Park is the most different in the terms of the dominant frequency (3996.95 ± 124.74 Hz) and lower frequency (1692.51 ± 80.77 Hz), of this population both these characters occupy the highest level compared to four other populations; however individuals from Curup occupy the lowest level on dominant frequency (2919.67 ± 67.76 Hz) and lower frequency (832.96 ± 32.42 Hz).Key words: Ranidae, Hylarana nicobariensis, bioacoustics